Analysis Of Hardening Products And Micro Structure Of Steel With Carbon Equivalent Variations And Cooling Oil Viscosity - listiyono listiyono; Subagijo Subagijo; sugeng hadi susilo (Journal of Evrímata: Engineering and Physics, 2023)
Heat Treament process has experiencing progress driven by improvements in science and technology. The heat treatment process has the aim to form the properties of metals with different work to be achieved in accordance with the objectives being made, heat treatment can also be used to change certain useful properties or for specific purposes for manufacture, such as: escalating machine ability characteristic, restoring the elasticity after cold work operations. The Purpose of the study to determine the effect of carbon equivalent and viscosity of cooling oil on the microstructure and hardness of steel in the hardening process. The method of the study is by doing a hardening process on the specimen with the temperature according to the thickness and composition of specimen. Then the cooling process is done using SAE 10 oil, SAE 40 oil, and SAE 90 oil. Then micro photo testing and hardness test are done with Vickers. The results of the study are, the carbon equivalent equivalent to violence results in a carbon equivalent value that has a significant effect on response because the P-value is smaller than alpha (P-value <α). On the influence of the cool oil viscosity to the hardness, the oil viscosity results have a significant effect on the response because the P-value is smaller than alpha (P-value <α). Whereas the interaction between variations in carbon equivalent and the viscosity of the coolant oil does not significantly influence the response because the P-value is greater than alpha (P-value> α). For the highest average hardness value on VCN 150 using SAE 10 oil at 486.5 HV and the lowest using SAE 40 oil at 450.7 HV, while on S45C steel the highest hardness using SAE 10 oil at 276.5 HV and the lowest hardness using SAE 40 oil is 249.7 HV. In the analysis of micro carbon equivalent structure and oil viscosity which has the highest average hardness value because it has a dominant martensitic structure. Whereas specimens that have ferrite structure still dominate compared to martensite which have the lowest mean hardness value.